Gamma Distributions Model For The Breast Cancer Survival Data Using Maximum Likelihood Method (International Journal of Engineering and Computer Science, 2014)
The breast cancer censored data of 254 patients was considered for the survival rate estimates. The data [12, 18] was treated at the chemotherapy department, Bradford Royal Infirmary for ten years. Here in this paper Gamma probabilitydistribution model is used to obtain the survival rates of the patients (see [2], [6], [13]). Maximum likelihood method has been used through unconstrained BFGS optimization method [5, 8, 9, 10] (BFGS-Broyden Fletcher-Goldfarb and Shanno Method) to find the parameter estimates and variance-covariance matrix for the Gamma distribution model. Finally the survivor rate estimates for the parametric Gamma probability model has been compared with the non-parametric (Kaplan-Meier-[15]) method.